18.9k views
0 votes
If f(x) = 2 ( x - 5)
Find: f19)
:(

User Efarley
by
5.8k points

2 Answers

6 votes

Answer:

28

Step-by-step explanation:

All you have to do is to plug the number that is in parentheses -> f(x), in this case, is 19 therefore all you really had to do is to plug 19 into the equation and then solve.

User Krx
by
4.9k points
5 votes

After evaluating the expression:f(x)=2(x−5);f(19 we get, f(x)=2x−10;19f.

Let's evaluate the expression:

f(x)=2(x−5);f(19)

We can evaluate the expression by distributing the terms and re-ordering them so the constants are on the left.

Steps to solve:

1. Distribute:

f(x)=2x−10;f(19)

2. Re-order terms so constants are on the left:

f(x)=2x−10;19f

Answer:

f(x)=2x−10;19f

Complete question below:

Let's evaluate the expression:f(x)=2(x−5);f(19

User Meeeee
by
5.0k points